Microspore culture and the performance of microspore derived doubled haploid in Brassica juncea (L.) (Bangladesh Journal of Agricultural Research, 2009)
The experiment was conducted at the Tissue Culture Laboratory as well as in the net house of Oilseed Research Centre, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur on microspore culture and the performance of microspore derived doubled haploid (DH) in Brassica juncea (L.). The variety BARI Sarisha II of B. junccea was used for microspore culture and 8 DH genotypes viz., BJDH 01, BJDH 05, BJDH ii, BJDH 12, BJDH 14, BJDH 17, BJDH 18, and BJDH 20 along with their parent Rajat collected from the Plant Research International, the Netherlands were used for performance evaluation. Four-day cold treatment at 6 Â°C along with bud size 3.0-3.1 mm of BARI Sarisha II showed better response in the embryonic development. Significant variation was observed for the different yield contributing characters among the DH genotypes along with their parent Rajat. All the DH genotypes were late both for days to flower and days to maturity compared to the parent. Most of the DH genotypes produced higher seed yield than the parent. The genotypes BJDII 14 (7 g) and BJDH 01(7 g) were bold seeded and almost double or more in 1000-seed weight compared to the parent. Total oil content of the DH genotypes (40.64-42.28) were significantly different from the parent (3 g). Oil content of BJDH 01 was almost 3% higher than the parent could be selected to incorporate in the future breeding program. Key Words: Microspore culture, doubled haploid, Brassica juncea. doi: 10.3329/bjar.v33i4.2290 Bangladesh J. Agril. Res. 33(4) : 571-578, December 2008